Ideologiese polisemie in verklarende Afrikaanse woordeboeke - Carstens, Adelia (Lexikos, 1994)
Ideological Polysemy in Monolingual Afrikaans DictionariesAfrikaans dictionaries are often criticised for their biased treatment of ideologically charged lemmas and senses. In order to redress ideological imbalances in a sensible way, theory-based strategies for the treatment of political-ideological lemmas / senses should be devised. Following German scholars such as Dieckmann, Hermanns and Strauss, the phenomenon manifested by the presence of variable ideological subsenses (within a single polysemic sense) is termed 'ideological polysemy' and is explored in depth. On the basis of specific articulations in the subsenses of political-ideological lexical items a typology of semantic schemas is proposed. Each typological category is represented by a schema for a prototypical member of that category. The schemas are applied diagnostically to selected entries in monolingual Afrikaans dictionaries in order to demonstrate how ideological bias may be identified and remedied by lexicographers.